Pengaruh Kemudahan, Keamanan, Kepercayaan dan E-Service Quality terhadap Keputusan Pembelian Secara Online pada E-Commerce Shopee - Amelia Eva Chrisanta; Nur Rokhman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
The purpose of this study was to determine the effect of easiness, security, trust and e-service quality on online purchasing decisions on e-commerce Shopee. Sampling was carried out using a non-probability technique with a purposive sampling method with the criteria that purchases or transactions at the Shopee online store had been carried out at least 2 times and from the age of 18 years (that age can make good decisions). The sample size in this study was 180 respondents. The results of this study indicate that easiness has a significant positive effect on online purchasing decisions on e-commerce Shopee. Security has a significant positive effect on online purchasing decisions on e-commerce Shopee. Trust has a significant positive effect on online purchasing decisions on e-commerce Shopee. E-Service Quality has a significant positive effect on online purchasing decisions on Shopee e-commerce. AdjustedR² shows that 70.3% of purchasing decisions are influenced by variables of easiness, security, trust and e-service quality, while the remaining 29.7% of purchasing decisions are influenced by other variables not included in the study.